2008
DOI: 10.1021/jp804156f
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Effects on the Intracluster Elimination Channels in M+(L)n, where M+ = Mg+ and Ca+, L = CH3OH, and NH3, and n = 2−6

Abstract: The methanol and ammonia solvated Ca+ or Mg+ clusters are known to go through intracluster H or CH3 eliminations which are typically switched on just below n = 6. By first principles calculations at the B3LYP/6-311+G** level, we have identified the transition structures, activation barriers, and energy changes in these reactions for clusters with 2−6 solvent molecules. The activation barrier is crucial to explain the previously reported experimental results. While increasing number of solvent molecules stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The actual roles of Mg(I) in chemical reactions are largely unexplored probably because detail experimental investigation of its chemical properties is challenging because of its metastable characters in condensed phases. Isolation of ions in the gas phase inside a mass spectrometer provides a great opportunity to examine the reactivity of transient intermediates on the molecular level. Although the subvalent Mg •+ is unstable in the condensed phases, gas-phase [Mg(H 2 O) n ] •+ clusters are isolable and exhibit rich redox chemistry that has attracted much experimental and theoretical interests in the past two decades. The solvation structure of [Mg(H 2 O) n ] •+ has been well-characterized; each cluster consists of a Mg 2+ and a hydrated electron solvated out from the 3 s orbital of the original Mg •+ center (reaction ). ,− The solvated electron can reduce a water molecule to liberate a hydrogen atom, leaving the hydroxide ion solvated in the cluster (reaction ).…”
Section: Introductionmentioning
confidence: 99%
“…The actual roles of Mg(I) in chemical reactions are largely unexplored probably because detail experimental investigation of its chemical properties is challenging because of its metastable characters in condensed phases. Isolation of ions in the gas phase inside a mass spectrometer provides a great opportunity to examine the reactivity of transient intermediates on the molecular level. Although the subvalent Mg •+ is unstable in the condensed phases, gas-phase [Mg(H 2 O) n ] •+ clusters are isolable and exhibit rich redox chemistry that has attracted much experimental and theoretical interests in the past two decades. The solvation structure of [Mg(H 2 O) n ] •+ has been well-characterized; each cluster consists of a Mg 2+ and a hydrated electron solvated out from the 3 s orbital of the original Mg •+ center (reaction ). ,− The solvated electron can reduce a water molecule to liberate a hydrogen atom, leaving the hydroxide ion solvated in the cluster (reaction ).…”
Section: Introductionmentioning
confidence: 99%
“…Direct, collision-induced bond cleavage was assumed to be responsible for the appearance of these fragments, which, given the comparatively low collision energies used by Kohler and Leary [18, 19], is probably going to be more efficient than ECID. A theoretical analysis by Chan et al [34] of the intracluster reaction channels available to [Ca(CH 3 OH) n ] 2+ and [Mg(CH 3 OH) n ] 2+ complexes concluded that switching arises from a more rapid decline in the reaction barrier to the elimination of H from the OH group than for the elimination of CH 3 . As n increases, solvation helps to stabilize the more polarizable CaOCH 3 + ion core [34].…”
Section: Resultsmentioning
confidence: 99%
“…A theoretical analysis by Chan et al [34] of the intracluster reaction channels available to [Ca(CH 3 OH) n ] 2+ and [Mg(CH 3 OH) n ] 2+ complexes concluded that switching arises from a more rapid decline in the reaction barrier to the elimination of H from the OH group than for the elimination of CH 3 . As n increases, solvation helps to stabilize the more polarizable CaOCH 3 + ion core [34].…”
Section: Resultsmentioning
confidence: 99%
“…In this work we explore the phenomenology of triple top-quark productions at the LHC and future 100 TeV collider. The triple top-quark production can be induced in many NP models which have extra heavy scalars or vector resonances with top-quark FVNI interactions [14,15]. In this paper we will assume that such new scalar or vector effects are indeed present, but that the energies available at present and near-future colliders lie below their typical NP scale Λ.…”
Section: Motivationmentioning
confidence: 99%